Insights into the control of optoelectronic properties in mixed-stacking charge-transfer complexes - Wang, Zongrui (2021)
Although cocrystallization has provided a promising platform to develop new organic optoelectronic materials, it is still a big challenge to purposely design and achieve specific optoelectronic properties. Herein, a series of mixed-stacking cocrystals (TMFA, TMCA, and TMTQ) were designed and synthesized, and the regulatory effects of the acceptors on the co-assembly behavior, charge-transfer nature, energy-level structures, and optoelectronic characteristics were systematically investigated. The results demonstrate that it is feasible to achieve effective charge-transport tuning and photoresponse switching by carefully regulating the intermolecular charge transfer and energy orbitals. The inherent mechanisms underlying the change in these optoelectronic behaviors were analyzed in depth and elucidated to provide clear guidelines for future development of new optoelectronic materials. In addition, due to the excellent photoresponsive characteristics of TMCA, TMCA-based phototransistors were investigated with varying light wavelength and optical power, and TMCA shows the best performance among all reported cocrystals under UV illumination.